Analysis of Added Value and Financial Feasibility of the Oys-ter Mushroom Agroindustry in Jember Regency - Rismawati, Rizki; Wardhana, Danu Indra; Nalawati, Ara Nugrahayu (Universitas Muhammadiyah Jember, 2024)
Jember Regency is one of the oyster mushroom producing districts in Java Province East. The relatively low price of raw oyster mushrooms means that it is not enough to support the economy of oyster mushroom farmers. Efforts to get added value from oyster mushrooms are by processing oyster mushrooms into processed products. The research aims to determine the level of financial feasibility of businesses and the added value of the oyster mushroom agro-industry in Jember Regency. The research was carried out using survey methods and in-depth interviews with oyster mushroom and industry experts as well as secondary data from literature, articles, journals and data from the Central Statistics Agency. Calculating added value using the Hayami method and calculating financial feasibility analysis of products that have high added value. The results of the added value analysis using the Hayami method show that the oyster mushroom product that has the highest added value is oyster mushroom broth amounting to IDR 172,688- (profit percentage 69.08%), oyster mushroom kebab IDR 47,751 (profit percentage 59.69%) and followed by crispy oyster mushrooms amounting to IDR 40,158 (profit percentage 57.37%) followed by oyster mushroom nuggets amounting to IDR 37,048 (profit percentage 55.57%). The financial feasibility results show that the oyster mushroom agro-industry in oyster mushroom broth products is feasible to run. These eligibility criteria show that at an interest rate of 9.75% the NPV value is IDR 626,388,706, the IRR value is 43.25%, the Net B/C Ratio is 1.12 production break-even point is 22,716 units per year, return on capital is 3.86 years. Sensitivity analysis of financial feasibility with an increase in raw material prices of 10%, 20% and 30% still shows a feasible decision. In the sensitivity analysis, a decrease in the product's selling price of 5% and 10% indicates that the decision is feasible, while a decrease in the product's selling price of 15% indicates that the decision is not feasible to carry out.